What is English music? - O'Loughlin, Niall (Muzikološki zbornik, 2007)
Many countries in the 19th century wanted to assert their national character, with music being one way of doing so. We can distinguish four ways in which in music national identity can be established: composers may use the folk music, they can base their music on folk music, they can set the words of a nation to music and the last possibility can be found in the idea of an association of certain music with specific events and festivities in a tradition. The author discusses in detail these four possibilities of the establishment of Englishness in music in 20th century.
Keywords: angleška glasba; Britten, Benjamin, 1913-1976; Elgar, Edward, 1857-1934; Finzi, Gerald, 1901-1956; folk music; ljudska glasba; Vaughan Williams, Ralph, 1872-1958; vokalna glasba